The Clearance of Thrombin-antithrombin and Related Serpin-enzyme Complexes from the Circulation: Role of Various Hepatocyte Receptors - Wells, Michael J.; Sheffield, William P.; Blajchman, Morris A. (Thrombosis and Haemostasis, 1999)
Peptide bond cleavage can herald the end of a protein’s active life, or its transformation from an inactive precursor to an active enzyme. If the newly activated protein is a proteinase, even a highly specific proteinase, then its activity must be regulated in order that unbridled cleavage and damage to the host organism do not ensue. Such regulation for many of the key serine proteinases of the coagulation, fibrinolytic, complement, and inflammatory pathways is provided by the inhibitory proteins of the serpin family.The serpins are a large family of over 100 proteins (1). Many are plasma proteins such as antithrombin (AT), α1-proteinase inhibitor (α-PI), α1-antichymotrypsin (α-AC), heparin cofactor II (HCII), plasminogen activator inhibitors (PAI) I and II, α2-antiplasmin (α2-AP) and proteinase nexin I (PN-1). While some serpins are readily recognizable as family members, solely by virtue of homology, others have been characterized in detail, particularly those that are suicide inhibitors of their cognate proteinases; enzymes that recognize and attack the reactive centre loop of the inhibitory serpins. The resulting serpin-enzyme complex (SEC) is comprised of the inhibitor, which is irreversibly inactivated by virtue of the cleavage of its reactive centre peptide bond, and the enzyme, which is reversibly inactivated by the formation of an acyl ester linkage between its active site serine and a serpin side chain. Thus, a stable, covalent, and stoichiometric complex resistant to denaturation is formed (2, 3).The reversible nature of the proteinase’s inactivation in the SEC means that while substantial regulation of the proteinase has been achieved, the organism has only prolonged the inevitable by forming the SEC. Because the SEC is only kinetically but not thermodynamically stable, given sufficient time it will break down, releasing cleaved serpin and active enzyme (4, 5). To prevent this, receptor-mediated mechanisms have evolved to effectively remove SECs from the circulation. Since the initial studies of Ohlsson, who investigated the clearance of α-PI-trypsin complexes in the circulation of dogs (6, 7), a large body of evidence has accumulated to indicate that SECs are cleared from the circulation more rapidly than their constituent serpins. This accelerated clearance seals the fate of the serpin-complexed proteinases, and prevents their release from SECs by sequestering the SECs inside cells, where they are catabolized. In this article, we review the available data with respect to the mechanisms involved in SEC removal from the circulation. Specifically, we address those proteins or molecules that have been reported to act as cellular receptors for SEC removal, and propose a model for SEC removal which includes several of the available candidate receptors. Where possible, we have focussed on the thrombin-antithrombin (TAT) complex, both because of our laboratory’s longstanding interest in antithrombin, and because of thrombin’s key role in haemostasis and thrombosis (8).